DARI MEMBACA MENDALAM KE PEMAHAMAN TERFRAGMENTASI: PRAKTIK PSEUDO-READING MAHASISWA DI ERA AI - Rizki Akbar Mustopa (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This study aims to explore the transformation of students’ academic reading practices in the age of artificial intelligence and its implications for critical thinking. Using a qualitative approach, data were collected from fourteen students across seven study programs through classroom observations and in-depth interviews. The findings reveal a shift from deep reading to fragmented reading, characterized by the tendency to access information in fragments without engaging with complete texts. The use of AI as a mediator of understanding reinforces this pattern, resulting in partial and superficial comprehension. This study identifies the phenomenon of pseudo-reading, a form of reading practice marked by a gap between perceived and actual understanding, which leads to an illusion of understanding and weakens critical thinking skills. These findings highlight the need to strengthen deep reading practices in academic learning in the AI era.